Pragmatics In Nominal Compounding (مجلة المنصور, 2022)
The present paper sheds light on the interdependent relation between compounding and pragmatics. Different approaches toanalyze compounds are examined .These are descriptive, semantic, typological, generativist, and pragmatic ;all confirmed that the set of compounding semantic relations is infinite. The reference to pragmatic information is crucial , since it leads both the speaker andhearer to question if compound interpretation can be formalized at all. The most important problems in any pragmatic theory tocompounding are redundant compounds , indirect compounding relations , and lack of generalization. Pragmatics and extralinguisticknowledge help the speaker and the listener reduce multiple ambiguities and inherent vagueness of these compound forms inways that a purely grammatical/semantic description does not. Pragmatic theories stress the importance of context in compoundinterpretation , social , cultural and stylistic background of the speaker and hearer.